Measuring Internet Access in Sub-Saharan Africa - Frankfurter, Zoe; Kokoszka, Klaudia; Newhouse, David; Silwal, Ani Rudra; Tian, Siwei (World Bank, Washington, DC, 2020)
The ability to access the internet has increasingly become an important tool for poverty reduction, especially during the Covid-19 pandemic. Despite its importance, measuring internet use in low-income settings is plagued by differences between data sources and lack of a consistent definition of what it means exactly to have internet access. This Note compares different data sources available for monitoring internet use in Sub-Saharan Africa (SSA) and examines a database of household surveys from 25 countries in the region. Three main findings emerge: (a) Household internet access may be less prevalent than commonly believed, (b) Access rates are particularly low for rural and poorer households, and (c) Many people in SSA access the internet through mobile phones rather than a home computer. Although many questions remain unanswered, household surveys are an important and underutilized resource to inform efforts to expand internet access in SSA.